The Role of Special Autonomy Funds (Otsus) in Improving the Human Development Index (HDI) of Aceh (Panel Data Study 2015–2024) - Shifa, Mutiara; Sani, Sri Rosmiati; Badli, Saiful; Hidayat, Muhammad Rahmat (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the effect of the Special Autonomy Fund (Otsus) on the Human Development Index (HDI) in Aceh during 2015–2024 using panel data from 23 districts/cities and a Fixed Effect Model (FEM). The analysis includes Otsus funds, education expenditure, health expenditure, and regional investment as independent variables. The findings indicate that Otsus funds significantly improve HDI, with varying impacts across regions. Education and health spending further strengthen this effect, highlighting the importance of effective and targeted budget allocation. The study provides insights for improving the management of Otsus funds to support sustainable human development in Aceh.